Characterization of Mortars from the Roman Cryptoporticus of Lisbon (Portugal) - Galacho, Cristina (2023)
The analytical characterization of mortar samples from the roman cryptoporticus of Lisbon, Portugal, was carried out by a multi-analytical archaeometric approach by means of Optical Microscopy (Stereo zoom and Petrographic microscope), Thermogravimetric analysis (TGA/DTG), X-Ray Diffraction (XRD), Scanning Electron Microscopy – Energy Dispersive X-ray Spectroscopy (SEM-EDS), Acid attack and Granulometric analysis. The Roman Cryptoporticus of Lisbon, also known as the “Roman Galleries of Rua da Prata” (Lisbon, Portugal), dates from the 1st century AD. The samples were divided into six groups, according to the most abundant type of aggregates and representative characteristics. This study provides valuable data on the production techniques and the raw materials used and their possible origin. Such characterization is necessary to create compatible repair mortars as part of a sustainable conservation methodology for the future conservation plan.